2007
DOI: 10.1111/j.1462-5822.2007.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Pili mediate specific adhesion of Streptococcus pyogenes to human tonsil and skin

Abstract: SummaryVery little is known about the biological functions of pili that have recently been found to be expressed by important Gram-positive pathogens such as Corynebacterium diphtheriae, Streptococcus agalacticae, S. pneumoniae and S. pyogenes. Using various ex vivo tissue and cellular models, here we show that pili mediate adhesion of serotype M1 S. pyogenes strain SF370 to both human tonsil epithelium and primary human keratinocytes, which represent the two main sites of infection by this human-specific path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(177 citation statements)
references
References 44 publications
7
169
0
1
Order By: Relevance
“…Group A streptococci are known to produce a plethora of adhesins, which vary among different serotypes. Examples include the M-protein, which is the major cell wall-associated virulence factor (2), adhesive pili that are assembled by the action of sortase enzymes (44), and the fibronectin-binding protein FbaB (40). These are all anchored covalently to the cell wall by the action of sortases that recognize a characteristic LPXTG sorting motif.…”
Section: Discussionmentioning
confidence: 99%
“…Group A streptococci are known to produce a plethora of adhesins, which vary among different serotypes. Examples include the M-protein, which is the major cell wall-associated virulence factor (2), adhesive pili that are assembled by the action of sortase enzymes (44), and the fibronectin-binding protein FbaB (40). These are all anchored covalently to the cell wall by the action of sortases that recognize a characteristic LPXTG sorting motif.…”
Section: Discussionmentioning
confidence: 99%
“…The capsule itself has been shown to interact directly with CD44 (55), thereby allowing paracellular transmigration (56). Moreover, fibronectin-binding protein SfbI and the GAS pilus have been described to be involved in keratinocyte adherence (50,51,57). However, conflicting data exist and most likely these interactions are not universal but rather serotype dependent (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…First, epithelial cells of the human larynxs and pharynxs have been extensively studied for plasminogen/ plasmin-mediated adherence and internalization mechanisms (22,33,50,51). Although it has been shown that GAS use paracellular transmigration through pharyngeal host cell monolayers (33), nothing is known about cell surface receptors binding to GAS surface-bound plasminogen/plasmin and the intracellular pathways exploited by the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of pili in streptococcal species has only been recently published [98-100]. Pili of S. pyogenes serotype M1 promote adhesion to human tonsil epithelium and primary human keratinocytes and the formation of biofilm [101,102], while the pili proteins of S. agalactiae facilitate adherence and invasion of brain endothelium [103]. The pilus operons promoting synthesis and assembly of pili are found in genomic islands such as the FCT pathogenicity island in S. pyogenes [98], the rlrA pathogenicity island in S. pneumoniae [100,104], and in novel genomic islands in S. agalactiae [99,105].…”
Section: Pili-specific Secretion/assembly Pathwaymentioning
confidence: 99%